2018
DOI: 10.1093/cvr/cvy179
|View full text |Cite
|
Sign up to set email alerts
|

Human peroxidasin 1 promotes angiogenesis through ERK1/2, Akt, and FAK pathways

Abstract: Our findings suggest a role of enzymatically active peroxidasin 1 as a pro-angiogenic peroxidase and a modulator of ERK1/2, Akt and FAK signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…The mechanism involves the oxidation of bromide to hypobromous acid (HOBr), which then promotes the cross link between specific methionine and hydroxylysine residues in the non-collagenous domain (NCD) to join two protomers of collagen IV (5). Other pathophysiological roles of peroxidasin have been suggested, such as antimicrobial defense (6,7), redox sensing through interaction with the transcription factor Nrf2 (8), promotion of angiogenesis (9) and kidney fibrosis (10,11). Homozygous deletion of peroxidasin causes eye defects (12) and high expression has been identified as a determinant of melanoma cell invasion (13).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism involves the oxidation of bromide to hypobromous acid (HOBr), which then promotes the cross link between specific methionine and hydroxylysine residues in the non-collagenous domain (NCD) to join two protomers of collagen IV (5). Other pathophysiological roles of peroxidasin have been suggested, such as antimicrobial defense (6,7), redox sensing through interaction with the transcription factor Nrf2 (8), promotion of angiogenesis (9) and kidney fibrosis (10,11). Homozygous deletion of peroxidasin causes eye defects (12) and high expression has been identified as a determinant of melanoma cell invasion (13).…”
Section: Introductionmentioning
confidence: 99%
“…VEGF downstream signaling pathways such as MAPKs, FAK, and AKT are known to regulate proliferation, migration, and tube formation (Cai et al, 2015; Medfai et al, 2019). For instance, ischemic stroke in adult mice is proven to be relieved by angiogenesis effect of PKM2 through activating the FAK signaling pathway (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, evidence have suggested that increased levels of lactate due to accelerating glycolysis can promote angiogenesis through upregulating the expression of hypoxia‐inducible factor‐1α (HIF‐1α) and vascular endothelial growth factor (VEGF; Porporato et al, 2012). VEGF mainly interacts with vascular endothelial growth factor receptor 2 (VEGFR2) and activates multiple downstream pathways, such as mitogen‐activated protein kinases (MAPKs), focal adhesion kinase (FAK), and protein kinase B (AKT) signaling pathways, which are all known to regulate proliferation, migration, and tube formation during angiogenesis (Cai et al, 2015; Medfai et al, 2019). In addition, Tie2 is a receptor tyrosine kinase that is expressed primarily on ECs and is required for angiogenesis and for promoting vascular maturation (Zacharek et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is remarkable to note that aforementioned OSS and OD collections were successfully used in DP in the recent years to address tens of diverse biomedical research questions or to teach histology and pathology to thousands of biomedical students. QuPath desktop software was used in various fields including oncology and immunology (19), cardiovascular diseases (20), or multiple sclerosis (21) (see other publications at https://github.com/qupath/qupath/wiki/Citing-QuPath). Cytomine web application was used by researchers in various fields including machine/deep learning (22), learning analytics, image analysis in nephrology [e.g., when combined with Icy; (14)], osteoarthritis (23), or lung cancer (24) (see other publications at https://uliege.cytomine.org/#publications).…”
Section: Discussionmentioning
confidence: 99%